2017
DOI: 10.1038/s41467-017-01773-0
|View full text |Cite
|
Sign up to set email alerts
|

Switching between H- and J-type electronic coupling in single conjugated polymer aggregates

Abstract: The aggregation of conjugated polymers and electronic coupling of chromophores play a central role in the fundamental understanding of light and charge generation processes. Here we report that the predominant coupling in isolated aggregates of conjugated polymers can be switched reversibly between H-type and J-type coupling by partially swelling and drying the aggregates. Aggregation is identified by shifts in photoluminescence energy, changes in vibronic peak ratio, and photoluminescence lifetime. This exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
151
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(162 citation statements)
references
References 70 publications
4
151
1
Order By: Relevance
“…We note that interchain coupling, i. e. H‐type aggregation, can be ruled out in this case, as opposed to other conjugated polymer materials aggregated by SVA . H‐type aggregation leads to a red‐shift of fluorescence spectra with an additional increase of the 0‐1/0‐0 peak ratio . The transition dipole moments of the individual monomers of the β‐phase effectively add up like in a J‐aggregate .…”
Section: Figurementioning
confidence: 79%
See 2 more Smart Citations
“…We note that interchain coupling, i. e. H‐type aggregation, can be ruled out in this case, as opposed to other conjugated polymer materials aggregated by SVA . H‐type aggregation leads to a red‐shift of fluorescence spectra with an additional increase of the 0‐1/0‐0 peak ratio . The transition dipole moments of the individual monomers of the β‐phase effectively add up like in a J‐aggregate .…”
Section: Figurementioning
confidence: 79%
“…One way to obtain such a direct connection is by avoiding ensemble averaging and measuring discrete mesoscopic regions of the PFO film. Such an approach can be experimentally achieved by bottom‐up assembly of mesoscopic aggregates, built from one molecule at a time, and investigating these particles with single molecule spectroscopic (SMS) techniques …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, coupling between chromophoric units that belong to different polymer chains and lie side‐by‐side gives rise to H‐coupling. The resulting changes in spectral signatures due to H‐aggregation compared to isolated polymer chains is diametrically opposed to J‐coupling, i.e., A 0–0 / A 0–1 decreases with enhanced H‐coupling 22a,23. We observed that the A 0–0 / A 0–1 value increases by almost 65% from 0.61 in monolayer to 1.00 in 7.5 nm film, reaches the highest value of 1.09 at ≈14 nm and gradually decreases on further thickness increase (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
“…In any ensemble, static and dynamic disorder control the interaction distances and the degree of electronic resonance between molecules, amplifying the effect of disorder broadening, which masks electronic coherences even in ultrafast experiments . Single‐molecule techniques have emerged as a route to study aggregation . With methods of controlled solvent‐vapor annealing, a few single molecules can be assembled to one single aggregate, probing the realm of single‐molecular mesoscopic structures with minimal disorder .…”
Section: Figurementioning
confidence: 99%